3 days grace. - Tan, Kenny Seah Hiang. (2010)
At a time when the local government is deciding on implementing filial piety laws, Sonny, a tough 38 year-old boxing instructor is located by a social worker to return to his ailing father after 17 years. Without caretakers and on such short notice, he is tasked to take care of his father for a period of three days while the authorities process the paperwork to have his father admitted into a nursing home.